DIVERSITY, DOMINANCY, AND PERIODICITY OF MOSQUITOES IN FILARIASIS ENDEMIC AREAS IN SAMBOREJO VILLAGE TIRTO DISTRICT PEKALONGAN REGENCY - Wibawaning Astuti, Raden Roro Upiek Ngesti (Indonesian Journal of Tropical and Infectious Disease, 2019)
Vector-borne mosquito diseases are still as a public health problem in the world, including in Indonesia.  Many of mosquitoes species are significantly as vectors of patogen, such as virus, bacteria, protozoan, and helminths due to human health. Samborejo Village is one of filariasis endemic areas and it is still in a high mf-rate. Each of mosquito species has a differential of distribution, bioactivities pattern, and type of habitat of their breeding sites  with others.  The objective of this study was to determine the diversity, dominancy, and periodicity pattern of mosquitoes during night time in Samborejo Village Tirto Distric Pekalongan Regency.  Mosquitoes collections were done by landing method, from 6 pm - 6 am of in an hour period of collection, for biting and resting  activities and also for indoor and outdoor collection respectively. Mosquitoes were then identified and the diversity was analized by Shannon-Wienner Index. The total number of each species was served in percent. Totally there were 339 collected mosquitoes, consisting of 165 (48.67%) females and 174 (51.33%) males. Of all, there were 4 species identified which were Culex quinquefasciatus  (92.1%), Culex tritaeniorhynchus (0.6%), Culex vishnui (1.8%), and Aedes aegypti (5.5%). Samborejo Village showed in low diversity with the index of 0.338, and Cx. quinquefasciatus to be the dominant species in this area. Culex quinquefasciatus also became the frequent species in each period of collection for indoor and outdoor, and it showed the indoor active biting at 9 pm, 01 am, and 03 am; furthermore, the outdoor active biting was  at midnight (00) and at 03 am. However,  Aedes mosquitoe was showed active biting in earlier, it was at 6 pm, 7 pm, and at 02 am.